Rules and regulations of The United Brothers' Birmingham Benefit Society (London : J.S. Forsaith & Son, Printers (T.U.), 1908)
1908 1908 1900s 18 pages 13 member shall have a printed report and balance sheet of the income and expenditure of the past year, for which he shall pay twopence; the secretary to be paid for lost time for preparing the same. That the secretary and auditors for the last quarter shall receive five shillings each for auditing and sharing out. 26. That these rules be open for alteration or amendment from time to time as the society see fit ; notice of the same to be given two meeting nights before quarterly night, stating the alterations intended to be brought forward. 27. That on the quarterly night in December the secretary shall appoint a convenient night for the division of surplus of the sick fund. 28. That the annual general meeting of this society be held on the second Saturday in January in each year. An attendance card to be given to all members on sharing-out night, the same to be placed in a box on general meeting night not later than 8.30 p.m., or be fined sixpence. That a committee consisting of seven members be elected every annual meeting night, they meet when summoned by the secretary to transact business, for which they shall receive sixpence each for attendance. 29. That the committee have power to grant assistance to members in distress for the purpose of paying their contributions; the amount required for this purpose to be taken from the funeral fund, but the total amount so granted shall not exceed the rate of one penny from each member a quarter. Any member receiving assistance from the fund shall not be entitled to receive any further assistance for a period of twelve months. Members are requested to read these rules carefully, as they will be strictly enforced. 345/7/2/2